A Gendered Perspective on Organizational Creation - Bird, Barbara; Brush, Candida (Entrepreneurship Theory and Practice, 2002)
Literature on the creation of organizations is often cast within a masculine gender framework. This paper draws from three theoretical perspectives to develop a new perspective that broadens the view of organizational creation by encompassing the relative balance of feminine and masculine perspectives in the entrepreneur's venture start-up process and new venture attributes. We elaborate the relatively less visible feminine and personal perspective and compare this with the traditional or masculine perspective. Important to the discussion is the distinction between biology (sex: male and female, man and woman) and socialized perspectives (gender: masculine and feminine). While research and the general public often use the concept of gender loosely to signify sex, we follow a more precise feminist distinction. The paper advances new concepts of gender-maturity (an individual difference) and gender-balance (an organizational quality).